(untitled) - Carlos Seré (Rome, 1996)
The work has relevance beyond its originally intended use for the livestock environment atudy. It can help national and international organizations and professionals in finding orientation in the world's livestock sector that is becoming increasingly complex. This work is now made available to the interested public because there is a recognized need for quantitative information on livestock production systems. As it satnds the study could provide enough guidance in the initial phases. In many aspects this atudy is a " first shot " and will need to be improved as the database will be enlarged and the methodology will be upgraded.
Keywords: animal industry